Hypertensive Retinopathy in Takayasu Arteritis. (19th July 2013) - Rodriguez, Amadeo R.; Rebello, Ryan; Khalidi, Nader
Abstract: A 26-year-old woman presented with painless vision loss secondary to hypertensive retinopathy in the setting of Takayasu arteritis and renal artery stenosis.